PENGARUH KEPEMIMPINAN LURAH TERHADAP KESADARAN MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KELURAHAN TEDDAOPU KABUPATEN WAJO - Syupriadi Mujibu; Supris Musiafir (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
Leadership is a person's ability to influence other people, in this case his subordinates, in such a way that other people want to do the leader's will even though he may not like it personally. (Sondang P. Siagian, 2002: If you look closely at the definition, you will see at least three things, namely: 1) A person who occupies a leadership position requires certain abilities that are not possessed by other human resources in the organization. 2) Participation as an important element in carrying out leadership, and 3) The ability to change the 'egocentrism' of subordinates to become 'organization-centric'. Community awareness is the attitude of a person voluntarily complying with all regulations and being aware of duties and responsibilities, according to the Big Indonesian Dictionary, awareness is awareness, a state of understanding, what is felt/experienced by someone.